Acacetin inhibits the tumor growth of human osteosarcoma cells through regulating Wnt/β-catenin and JNK signaling pathways - Mengqi Wei (Journal of Functional Foods, 2022)
Osteosarcoma (OS) is the most common primary malignant bone tumor with high lung metastasis and mortality rate. Neo-adjuvant chemotherapy combined with limb salvage is the main treatment strategy for OS. However, because of the tolerance to conventional chemotherapy and the cell toxicity of chemotherapy drugs, new drugs with lower toxicity for OS are urgently needed. Acacetin is a natural flavonoid compound that has inhibitory effects on many kinds of tumors. Herein, we explored the impact of acacetin on OS cell growth in vitro and in vivo. We discovered that acacetin suppressed the proliferation, migration and invasion, while promoted the apoptosis of OS cells. Notably, acacetin had little impact on proliferation and apoptosis of human normal cells. Furthermore, we confirmed that acacetin repressed the growth and metastasis of OS in xenograft mouse model in vivo. Mechanically, we discovered that acacetin activated JNK pathway and inactivated Wnt/β-catenin pathway. β-catenin over-expression or JNK inhibitor SP600125 was able to partially neutralize acacetin-induced inhibitory effect on OS cells. To sum up, our study implies that acacetin may inhibit tumor growth of human OS cells through regulating Wnt/β-catenin and JNK signaling pathways.